Literature review: hyperbaric oxygen therapy on mucormycosis infection in oral cavity - Laihad, Fanny Margaretha; Sudiana, I Ketut; S, M Guritno (Folia Medica Indonesiana, 2017)
Mucormycosis infection is an invasive, acute and rapidly progressing fungal infection with high mortality rate unless it was identified promptly. Oral manifestations of these infections, some times appeared as palatal ulcer and can be triggered by tooth extraction on maxilla or mandibula in which the organ is not cured but even damage the gingival and alveolar bone. Hyperbaric oxygen (HBO) therapy is the administration of 100% pure oxygen in a pressurized room more than 1 atmophere that can be used for therapy of mucormycosis infection in oral cavity. The aim of this study is to analyze the use of hyperbaric oxygen therapy on mucormycosis infections in oral cavity in 30 journals and 1journal of suspected case of mucormycosis infection post dental extraction from 1980 until 2016. Hyperbaric oxygen therapy was used as the last and adjunctive therapy after antifungal and surgery in 30 jounals but in 1 suspected case, hyperbaric oxygen therapy was given earlier. The need for consideration to provide early HBO therapy in case of mucormycosis infection in oral cavity will improve prognosis and survival rate of the patient.